Manual de seguridad y salud del trabajo en las unidades de campo de la Carrera de Pecuaria- ESPAM MFL. - Moreira Benavides, Marcos Horacio (2015)
The objective of this research was to develop a manual safety and health including the prevention of occupational hazards incidents in the Field Units Livestock Career Polytechnic College Agricultural Manuel Felix Lopez Manabi - ESPAM MFL; to carry out this research, various activities were carried out: identification of processes and activities of the Field Units by applying interviews to the unit coordinators and direct observation; Description of occupational hazards by implementing surveys of the 18 workers of the Field Units, as well as the risk matrix established by the Ministry of Labor Relations that allowed detailing the risks that arise in the Incubator and Hato Porcino Bovine; manual safety and health was designed, describing the activities with an impact of risks identified through the techniques applied, these activities were detailed in the matrices HIRA (Hazard Identification and Risk Assessment); and finally, the socialization of the Manual was made with the employees in the unit to contribute to the prevention of occupational risks. In conclusion, the applicability of the manual safety and health of the Field Units Livestock Career - ESPAM MFL serve as an instrument for the prevention of risks in the development of each of the activities of the Incubator, Hato beef and pork.